Paralytic ileus as the presenting symptom for Guillain–Barré syndrome: a case report. Issue 4 (October 2020) - Lee, Kuang-Heng; Ho, Tsung-Han; Lee, Jiunn-Tay; Lin, Li-Fan; Chang, Wei-Chou; Shih, Chang-Chih; Yang, Fu-Chi
Guillain–Barré syndrome (GBS) is an acute neuroimmunological disorder characterized by rapidly ascending symmetrical limb weakness, areflexia, and sensory deficits. Approximately 65% of patients with GBS present with autonomic dysfunction, which commonly occurs in advanced stages. However, paralytic ileus, a sign of gastrointestinal dysautonomia, is rare as the presenting feature in GBS before motor weakness becomes evident. We report the case of a 54-year-old man admitted to the Emergency Department with paralytic ileus as the prodromal feature in early-stage GBS. Total parenteral feeding and prokinetic use were initiated, but no clinical improvement was observed. The patient showed rapid progression to quadriplegia, which was ultimately determined to be respiratory muscle failure requiring mechanical ventilation and intensive care unit admission. He underwent 5 days of intravenous immunoglobulin therapy and muscle strength was partially improved thereafter. However, the patient's enteral nutritional support was undesirable because of persistent poor gastric emptying complicated by fungemia and profound sepsis throughout the hospital course. Finally, he died 1 month after admission. Ignorance of this unusual prodrome to GBS could result in delayed treatment, along with potential progression to life-threatening events. Early recognition of GBS and prompt immunotherapy are critical for reducing morbidity and mortality.